PENINGKATAN HASIL BELAJAR PADA MATA PELAJARAN PKN MELALUI METODE PEMBELAJARAN CARD SORT (KARTU SORTIR) PADA SISWA KELAS IV SDN 15 KUMANIH ATEH - ELFIMAR ELFIMAR (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes of Class IV SDN 15 students Kumanih Ateh in learning in PKN Subjects it was found that learning outcomes in PKN Subjects were still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about the improvement of learning outcomes in PKN subjects sub The importance of carrying out rights and obligations in a balanced manner in people's lives through the Card Sort Learning method in Class IV SDN 15 Kumanih Ateh Sawahlunto City.This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 12 students of Class IV SDN 15 Kumanih Ateh. Research data were collected using observation sheets and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been it can be concluded that the Card Sort Learning method can improve learning outcomes in PKN sub subjects The importance of exercising rights and obligations in a balanced manner in the life of the community at SDN 15 Kumanih Ateh. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 56.15 (enough) increased to 84.04 (good) with an increase of 27.89%.stated,